Employing Precision Livestock Production to Strengthen Dairy animal Management - Taskeen Zaidi, Jai prakash gupta, Pawan Bhambu (Revista Electronica de Veterinaria, 2024)
This research offers a comprehensive analysis of modern dairy production that takes two important factors. We investigate the complex interactions that exist between people and dairy animals, with a particular emphasis on small ruminants, buffaloes, and dairy cattle. By bringing attention to the intricacies of these relationships, we can get important knowledge that will help to increase productivity and improve animal welfare. This research explores the field of Accurate Livestock Farming (ALF) and how it has changed the dairy industry. An examination of methods for assessing health, such as detecting lameness and mastitis, is provided in relation to dairy cattle. The definition of ALF technologies is expanded by including tiny ruminants in the discussion. Therefore, to increase the effectiveness and efficiency of handling, tiny ruminants, tailored intervention training programs are also required. With its emphasis on the critical interactions between the animal and human elements and its demonstration of the critical role that accuracy technology will play in influencing the direction of the dairy industry, this synthesis advances our comprehension of the dynamic field of dairy farming.